1991
DOI: 10.1128/iai.59.12.4517-4523.1991
|View full text |Cite
|
Sign up to set email alerts
|

The outer membrane of Pasteurella multocida 3:A protects rabbits against homologous challenge

Abstract: The protective efficacy of a vaccine purified from the Pasteurella multocida 3:A outer membrane (OM) was evaluated in rabbits by homologous challenge. Twenty-seven rabbits were divided into four groups: 1, vaccinated with OM and challenged; 2, nonvaccinated and challenged; 3, vaccinated with OM only; and 4, nonvaccinated and not challenged. Rabbits were immunized intranasally with 1 mg of OM protein on days 0, 7, 14, and 35, challenged intranasally on day 49, and killed on day 63. Mortality rates were 0, 67, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Protein H is highly immunogenic, and antibodies directed against the protein are able to inhibit binding to respiratory mucosal surfaces (25,26). A 50-kDa OMP with antiphagocytic activity was able to protect turkeys from lethal challenge (37), while a monoclonal antibody against a 37.5-kDa protein demonstrated protection against homologous challenge (24). The immunogenic 16-kDa P6-like OMP is expressed by all 16 serotypes of P. multocida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein H is highly immunogenic, and antibodies directed against the protein are able to inhibit binding to respiratory mucosal surfaces (25,26). A 50-kDa OMP with antiphagocytic activity was able to protect turkeys from lethal challenge (37), while a monoclonal antibody against a 37.5-kDa protein demonstrated protection against homologous challenge (24). The immunogenic 16-kDa P6-like OMP is expressed by all 16 serotypes of P. multocida.…”
Section: Discussionmentioning
confidence: 99%
“…Few OMPs of P. multocida have been characterized. A 37-kDa OMP is thought to be the major porin (7,26), a 50-kDa OMP was reported to have antiphagocytic activity (37), and Lu et al (24) demonstrated that a monoclonal antibody against a 37.5-kDa OMP was protective in animal models. OM antigens expressed under iron-limiting conditions have been identified and appear to play a role in immunity against pasteurellosis (8,32).…”
mentioning
confidence: 99%
“…Pasteurella multocida is an important bacterial pathogen which causes a common and widespread respiratory infection leading to great losses among rabbit populations (Lu et al, 1991). Prevention is the most likely and potential means to control pasteurellosis through vaccination which is critically important tool in preventing the disease (Amina el-Bayomy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental vaccines have included inactivated whole bacteria, streptomycin-dependent live P multocida mutants, lipopolysaccharide, outer membrane proteins (OMP), potassium thiocyanate (KSCn) extract, and Escherichia coli J5 bacterin. [9][10][11][12][13][14][15][16] Various routes of delivery have been used, including parenteral, oral, and intranasal routes. Enhanced resistance has developed with use of several of these experimental vaccines; however, none have been successful enough to warrant development and use against natural pasteurellosis.…”
mentioning
confidence: 99%
“…Oil adjuvants have commonly been used in experimental P multocida vaccines administered via parenteral injection. 12,13 For mucosal immunity, however, cholera toxin (CT) is an effective adjuvant for mucosal vaccines against several infectious agents, including bacteria and parasites. [16][17][18] Recently, Suckow et al 19 demonstrated that rabbits intranasally immunized with P multocida serogroup-D KSCn extract containing CT had greater antibody responses and enhanced resistance to experimental challenge, compared with rabbits immunized with KSCn alone.…”
mentioning
confidence: 99%